2011
DOI: 10.1093/ndt/gfq851
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arteriovenous fistula formation on arterial stiffness and cardiovascular performance and function

Abstract: AVF formation resulted in a sustained reduction in arterial stiffness and BP as well as an increase in LVEF. Overall, post-AVF adaptations might be characterized as potentially beneficial in these patients and supports the widespread use of native vascular access, including older or cardiovascular compromised individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(108 citation statements)
references
References 30 publications
5
100
1
2
Order By: Relevance
“…This physiology is in part appreciated in patients receiving peripheral arteriovenous fistula for dialysis, with a reduction in SVR of 17% soon after fistula formation. 3 Antihypertensive drug therapy has disparate effects on hemodynamics depending on drug class The central iliac arteriovenous anastomosis is a unique solution to hypertension in patients with reduced aortic compliance, a situation where neurohormonal interventions would not be anticipated to have substantial impact. The reduction in BP and SVR that we report is immediate and far greater in magnitude than alternative treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…This physiology is in part appreciated in patients receiving peripheral arteriovenous fistula for dialysis, with a reduction in SVR of 17% soon after fistula formation. 3 Antihypertensive drug therapy has disparate effects on hemodynamics depending on drug class The central iliac arteriovenous anastomosis is a unique solution to hypertension in patients with reduced aortic compliance, a situation where neurohormonal interventions would not be anticipated to have substantial impact. The reduction in BP and SVR that we report is immediate and far greater in magnitude than alternative treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…These data state that the lower mortality of these patients with AVF, may be due to factors beyond VA associated infections and dysfunctions [152]. However, data from 1996 to 2006 collected from DOPPS indicate a growing use of catheters in many countries [153].…”
Section: Final Remarks and Conclusionmentioning
confidence: 98%
“…A larger study (40 active patients and 40 controls) showed that at 6 months the AVF group showed a significant reduction in the office BP as well as in the ABP levels. 16,17 The novel technique was shown to be effective, but a third of AVF patients developed ipsilateral venous stenosis, which resolved after stenting or venoplasty. This unique promising procedure awaits further testing and additional research studies.…”
Section: Central Arteriovenous Coupler Therapy For Resistant Hypertenmentioning
confidence: 99%